2017
DOI: 10.3389/fmicb.2017.01348
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of the Nitrogen-Fixing Rhizobium sullae Type Strain IS123T Focusing on the Key Genes for Symbiosis with its Host Hedysarum coronarium L.

Abstract: The prominent feature of rhizobia is their molecular dialogue with plant hosts. Such interaction is enabled by the presence of a series of symbiotic genes encoding for the synthesis and export of signals triggering organogenetic and physiological responses in the plant. The genome of the Rhizobium sullae type strain IS123T nodulating the legume Hedysarum coronarium, was sequenced and resulted in 317 scaffolds for a total assembled size of 7,889,576 bp. Its features were compared with those of genomes from rhiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…This study demonstrated that nitrogen‐fixing bacteria occupied a dominant position in the roots of xeric leguminous plants, but also that many non‐nitrogen‐fixing microbes were present. These results confirmed that nitrogen‐fixing rhizobia co‐exist with other bacteria in the roots of desert xeric leguminous plants, which is consistent with previously reported results, where isolated cultures were used to assess the Rhizobium strains of leguminous plants (Sablok et al., 2017; Toniutti et al, 2017; Yates et al., 2015). This study showed that in addition to dominant nitrogen‐fixing rhizobia, there were also other, nonsymbiotic endophytes in the roots of Hedysarum plants.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study demonstrated that nitrogen‐fixing bacteria occupied a dominant position in the roots of xeric leguminous plants, but also that many non‐nitrogen‐fixing microbes were present. These results confirmed that nitrogen‐fixing rhizobia co‐exist with other bacteria in the roots of desert xeric leguminous plants, which is consistent with previously reported results, where isolated cultures were used to assess the Rhizobium strains of leguminous plants (Sablok et al., 2017; Toniutti et al, 2017; Yates et al., 2015). This study showed that in addition to dominant nitrogen‐fixing rhizobia, there were also other, nonsymbiotic endophytes in the roots of Hedysarum plants.…”
Section: Discussionsupporting
confidence: 91%
“…They can infect and live on leguminous plants, form nodules in their roots, supply the nitrogen nutrients needed by leguminous plants during growth through nitrogen fixation from soil and air, and build a mutualistic symbiotic relationship with leguminous plants (Batut & Boistard, 1994; He & Zhu, 1998). This interaction is based on unique transcription and the signal transmission of symbiotic genes of the host plant and rhizobia, which in turn trigger the corresponding organogenesis and adaptive physiological response of the host plant (Sablok et al., 2017). Various studies have shown that R. sullae is an efficient nitrogen‐fixing rhizobium that can enter the root system of the genus Hedysarum and establish a mutually beneficial symbiotic relationship with the host (Yates et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant is still occurring both as a cropped legume and as a spontaneous weed in Mediterranean habitats, and it is particularly tolerant to drought and alkalinity. The genome sequences of two other strains of the same bacterial species have been published, including that of the type strain IS123 (2) isolated in southern Spain from its host growing in the wild, and that of strain WSM1592 (3), isolated from cropped sulla on the island of Sardinia (Italy). The present isolate, HCNT1 (=IMAP 801, =ATCC 43676) (4), was isolated from root nodules of its host collected under spontaneous conditions in the highly calcareous pliocenic clays near Volterra (Tuscany, Italy).…”
Section: Genome Announcementmentioning
confidence: 99%
“…The role of rhizobia has always been the main research focus, and its most notable feature lies in its ability to establish a compatible interaction with molecules in the root of the host plant. This interaction depends on the expression of symbiosis-specific genes involving in gene compiling and signal output, and genes that can eventually trigger the unique organogenesis and other corresponding physiological responses of the host plants [ 35 ]. One study has shown that Rhizobium sullae is a highly efficient nitrogen-fixing rhizobium that can form symbiotic associations with Hedysarum plants [ 36 ].…”
Section: Introductionmentioning
confidence: 99%